CO2 leakage simulation: Effects of the decreasing pH to the survival and reproduction of two crustacean species. (June 2019) - Conradi, M.; Sánchez-Moyano, J.E.; Galotti, A.; Jiménez-Gómez, F.; Jiménez-Melero, R.; Guerrero, F.; Parra, G.; Bonnail, E.; DelValls, T.Á.
Abstract: The effects of CO2 -related acidification on two crustacean populations, the isopod Cyathura carinata and the amphipod Elasmopus rapax, were studied. Three pH levels were tested: artificial seawater without CO2 injection and two levels of reduced pH. Even though RNA:DNA ratio was reduced for both species, no statistical significant differences were found between the control and the treatments. Both species experienced a reduction in survivorship, longevity and the body length of surviving animals; although the impairment observed in E. rapax was more severe than in C. carinata . The long life span isopod and the short life span amphipod experienced a high degree of impairment in the reproduction, likely due to the reallocation of resources from reproduction to body maintenance and increasing survival by postponing the brood production. Regardless of the underlying processes and the energetic pathways, both experienced failure to reproduce, which could lead to the local extinction of these species. Highlights: Both species show reduction in their fitness when exposed to CO2 acidification scenarios. The isopod Cyathura carinata survives at pH as low as 6.5, not the amphipod Elasmopus rapax The impairment observed in E. rapax was more severe than in C. carinata. Regardless the lengths of the lifespan, both species were unable to produce offspring.